Study Materials for the Purpose of the Introductory Program of Students Enrolled in Class 10 of the Islamic High School/المواد الدراسية لغرض البرنامج التمهيدي (Matrikulasi) لدى الطلاب المعيين في الصف العاشر من المدرسة الثانوية الإسلامية - Abdul Manaf, luthfi (JURNAL IJ-ATL, 2018)
This research deals with the application of the Matrikulasi program for students enrolled in the tenth grade of Islamic secondary school and how to choose and design subjects.يتناول هذا البحث كيفية تطبيق البرنامج التمهيدي (Matrikulasi) لدى الطلاب المعيين في الصف العاشر من المدرسة الثانوية الإسلامية وكيفية اختيار المواد الدراسية وتصميمها.